2002
DOI: 10.1159/000059400
|View full text |Cite
|
Sign up to set email alerts
|

IgE Reactivity to Profilin in Pollen-Sensitized Subjects with Adverse Reactions to Banana and Pineapple

Abstract: Background: The so-called ‘latex-fruit syndrome’ is a well-documented phenomenon in cross-reactive allergies. By contrast, there is a lack of information about allergy to exotic fruits in patients with a predominant pollen sensitization. Since the ubiquitous protein profilin has been identified as an allergen in natural rubber latex as well as in pollen-related foods, the aim of this study was to investigate the role of profilin in allergy to certain exotic fruits. Methods: Recombinant profilins from banana an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 20 publications
4
45
1
1
Order By: Relevance
“…Sera from patients with pollen allergy sensitized to profilin show IgE cross-reactivity with fruits and vegetables. Profilin has been implicated in the birch-Rosaceae fruit and the birch-mugwort-celery-spice syndrome [11, 12], and several studies concluded that this protein can also play a role in patients allergic to a variety of other foods [6, 11, 13, 14, 15, 16, 17, 18, 19, 20, 21]. Results of recent studies suggest that IgE antibodies to profilin in foods have little or no clinical relevance [22, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Sera from patients with pollen allergy sensitized to profilin show IgE cross-reactivity with fruits and vegetables. Profilin has been implicated in the birch-Rosaceae fruit and the birch-mugwort-celery-spice syndrome [11, 12], and several studies concluded that this protein can also play a role in patients allergic to a variety of other foods [6, 11, 13, 14, 15, 16, 17, 18, 19, 20, 21]. Results of recent studies suggest that IgE antibodies to profilin in foods have little or no clinical relevance [22, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Patients sensitized to profilins, a family of highly conserved cytoskeletal proteins, may show allergic reactions to pollens and foods from a variety of plants (17)(18)(19)(20)(21)(22)(23)(24)(41)(42)(43)(44)(45)(46). We report the engineering and characterization of a vaccine for the treatment of those patients who exhibit broad pollen and plant food cross-reactivities due to profilin sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…23), lychee (rLit c 4), cashew nut (rAna c 1), carrot (rDau c 4), hazelnut (rCor a 2), and banana (rMus xp 1; Ref. 19) were expressed in Escherichia coli and purified using poly-L-proline-loaded agarose columns (Amersham Bioscience) as described (22). Natural (n) timothy grass pollen profilin (nPhl p 12) was purified from pollen grains by affinity chromatography using poly-L-proline-loaded agarose (Amersham Bioscience) as described (17).…”
Section: Purification Of Pollen and Plant Food Profilinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hev b 8 seems to be involved in the latex-fruit syndrome as cross-reactivity could be demonstrated to profilins from celery tuber [46], banana and pineapple [47], and bell pepper [27]. …”
Section: Hev B 8 (Profilin)mentioning
confidence: 99%